2011
DOI: 10.1038/bmt.2011.26
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of children requiring intensive care following haematopoietic SCT for primary immunodeficiency and other non-malignant disorders

Abstract: Haematopoietic SCT (HSCT) is curative for many children with primary immunodeficiencies or other nonmalignant conditions. Outcome for those admitted to intensive care following HSCT for oncology diagnoses has historically been very poor. There is no literature available specifically regarding the outcome for children with primary immunodeficiency requiring intensive care following HSCT. We reviewed our post-HSCT admission to intensive care over a 5-year period. A total of 111 children underwent HSCT. Median ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 25 publications
5
34
3
Order By: Relevance
“…The association between infections and posttransplant mortality has been reported in PID patients in the medical literature. 18,[21][22] In our study, death related to GVHD was associated with infectious complications in 3 patients. In addition, 2 patients died from intracranial hemorrhage in this study (Table 3).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The association between infections and posttransplant mortality has been reported in PID patients in the medical literature. 18,[21][22] In our study, death related to GVHD was associated with infectious complications in 3 patients. In addition, 2 patients died from intracranial hemorrhage in this study (Table 3).…”
Section: Discussionmentioning
confidence: 86%
“…This percentage is lower than in previously reported studies. 3,21 Cole and associates 21 reported that 35% of children had at least 1 intensive care unit admission. Two of 6 patients who needed admission (33%) were discharged (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Data from a previous study demonstrated that HSCT patients with underlying non-malignant conditions had an increased risk for PICU admission. [21] In a large study of 111 critically ill children with primary immunodeficiency undergoing HSCT, 39 (35%) children required a total of 58 PICU admissions. [21] This is in contrast with only 12 (20%) of our 59 infants requiring emergent PICU admissions.…”
Section: Discussionmentioning
confidence: 99%
“…[21] In a large study of 111 critically ill children with primary immunodeficiency undergoing HSCT, 39 (35%) children required a total of 58 PICU admissions. [21] This is in contrast with only 12 (20%) of our 59 infants requiring emergent PICU admissions. One possible reason for this difference is that in the prior study, 104 (94%) children received chemotherapy prior to their HSCT, whereas less than half of our patients received immunosuppression (generally consisting of calcineurin inhibitor and/or rabbit anti thymocyte globulin therapy).…”
Section: Discussionmentioning
confidence: 99%
“…For those patients requiring additional support through the transplant period, improvement in paediatric intensive care, close liaison between BMT and PICU teams, and earlier interventions are leading to improved outcomes of patients receiving HSCT but needing to go to PICU. Survival rates are now approaching up to 60%, better survival for those who receive only invasive ventilation and worse survival for those with multi organ failure [56].…”
Section: Severe Combined Immunodeficiencymentioning
confidence: 99%